Consensus statement on blocking interleukin-6 receptor and interleukin-6 in inflammatory conditions: an update - Aletaha, Daniel; Kerschbaumer, Andreas; Kastrati, Kastriot; Dejaco, Christian; Dougados, Maxime; McInnes, Iain B; Sattar, Naveed; Stamm, Tanja A; Takeuchi, Tsutomu; Trauner, Michael; van der Heijde, Désirée; Voshaar, Marieke; et al. (Annals of the rheumatic diseases, 2023)
BACKGROUND: Targeting interleukin (IL)-6 has become a major therapeutic strategy in the treatment of immune-mediated inflammatory disease. Interference with the IL-6 pathway can be directed at the specific receptor using anti-IL-6Rα antibodies or by directly inhibiting the IL-6 cytokine. This paper is an update of a previous consensus document, based on most recent evidence and expert opinion, that aims to inform on the medical use of interfering with the IL-6 pathway. METHODS: A systematic literature research was performed that focused on IL-6-pathway inhibitors in inflammatory diseases. Evidence was put in context by a large group of international experts and patients in a subsequent consensus process. All were involved in formulating the consensus statements, and in the preparation of this document. RESULTS: The consensus process covered relevant aspects of dosing and populations for different indications of IL-6 pathway inhibitors that are approved across the world, including rheumatoid arthritis, polyarticular-course and systemic juvenile idiopathic arthritis, giant cell arteritis, Takayasu arteritis, adult-onset Still's disease, Castleman's disease, chimeric antigen receptor-T-cell-induced cytokine release syndrome, neuromyelitis optica spectrum disorder and severe COVID-19. Also addressed were other clinical aspects of the use of IL-6 pathway inhibitors, including pretreatment screening, safety, contraindications and monitoring. CONCLUSIONS: The document provides a comprehensive consensus on the use of IL-6 inhibition to treat inflammatory disorders to inform healthcare professionals (including researchers), patients, administrators and payers.
Keywords: receptory interleukinu-6; Receptors, Interleukin-6; zánět; biological therapy; Still's Disease, Adult-Onset; Interleukin-6; Adult; revmatoidní artritida; Arthritis, Rheumatoid; Stillova nemoc dospělých; lidé; dospělí; Inflammation; rheumatoid arthritis; interleukin-6; Humans; autoimmune diseases; COVID-19